PEMANFAATAN GEDEBOG KERING DALAM PEMBELAJARAN SENI LUKIS KOLASE BAGI SISWA KELAS XII IPA 1 MAN MAJENANG KABUPATEN CILACAP - RAMADHANI, JANIYAH (Universitas Negeri Semarang, 2015)
The formulation of the issues examined in this study are (1) how the process of utilization of dry gedebog in learning art collage for students Class XII Science 1 MAN Majenang Cilacap ?, (2) how the work dried gedebog utilization in learning collage painting for students of class XII IPA 1 MAN Majenang Cilacap ?, (3) what are the constraints faced in the implementation of activities in the utilization of dry gedebog collage art learning for students of class XII IPA 1 MAN Majenang Cilacap? The method in this research is descriptive qualitative. The target in this study is the use of dry gedebog in learning for students of painting collage Class XII IPA 1 as many as 24 students. Implementation of learning produces a variety of collage paintings are quite unique, interesting, varied and showed good results.